Pembiasaan Adab Islami (Salam, Doa, dan Sopan Santun) dalam Membentuk Karakter Anak di Daycare Minhajul Haq - Rizaldy Alpiansyah; Irfan Alkhotiri; zamzam zamaludin zamzam zamaludin (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
Instilling Islamic manners is the process of developing attitudes and behaviors in accordance with Islamic teachings through repeated learning. The process of habituation is synonymous with repetition, an activity carried out repeatedly that eventually becomes a habit. Instilling good character in accordance with the Quran and Sunnah requires efforts from teachers and parents, one of which is by instilling positive habits in children. This research was conducted at Minhajul Haq daycare and aimed to describe the methods of instilling Islamic manners by teachers and caregivers in instilling character in children. The subjects were the daycare principal and the teachers and caregivers. This study used a qualitative descriptive approach. Data collection techniques used in this study included interviews, observation, and documentation. The collected data were then processed and presented as a complete set of data. Based on the results of the research that has been conducted, it can be concluded that the habituation method in instilling Islamic manners (greetings, prayers and politeness) in Minhajul Haq daycare can be seen from the habituation of Islamic manners (greetings, prayers and politeness) in daycare through routine, programmed and incidental activities that can bring out good character values ​​in children.